Imagining Ecologies through Sound: An Historic-ecological Approach to the Soundscape of the Mississippi Flyway - Hui, Alexandra (MUSICultures, 2019)
This paper documents an example of the development of what I term “imagined ecologies,” an individual or community’s understanding of themselves as part of an ecological system. An examination of game call instructions and training records offers a strategy for understanding the soundscape of the Mississippi Flyway. I show that the sounds made and ways of listening to them — by humans and non-humans — was critical to the formation of an imagined ecology that saw nature as, paradoxically, a resource that could be managed and harvested but not quite replicated.